PRE-SERVICE SECONDARY MATHEMATICS TEACHERS’ UNDERSTANDING OF ABSOLUTE VALUE - Aziz, Tian Abdul; Supiat, Supiat; Soenarto, Yohanes (Jurnal Cakrawala Pendidikan, 2019)
This study aims to give a comprehensive account of pre-service secondary mathematics teachers’ understanding of absolute value. Thirty two-item absolute value understanding test was developed and administered to thirty-eight students attending mathematics education department at one private university in Jakarta City, Indonesia. Five of them were selected purposively and interviewed to gain deep information and confirm their written responses in the test. We find that most participants struggled with the absolute value task. There are inconsistencies of the definition of absolute value expressed by them. Besides, typical mistakes made are: (a) removal of absolute value bars; (b) focus heavily on rules; (c) conversion of absolute value bars to parentheses; (d) exclusion of number inside absolute value bars; (e) poor algebraic manipulation; and (f) inability to draw absolute value graph. Based on the findings, the most common cause of mistakes made by the participants is didactical contract in mathematics teaching and learning. Limitation and implications of the study are presented.